Female pelvic medicine and reconstructive surgery practice patterns: IUGA member survey - Ghoniem, Gamal; Hammett, Jessica (International Urogynecology Journal, 2015)
Introduction and hypothesis The purpose of this study is to describe the current practice patterns of the International Urogynecological Association (IUGA) members regarding the diagnosis, evaluation, and surgical management of stress urinary incontinence (SUI) and pelvic organ prolapse (POP). Methods A 30-item internet-based survey was sent to IUGA members. Response to the survey was voluntary, and subjects answered questions regarding demographics, the evaluation of POP and SUI, including urodynamics (UDS) testing, preferred management of POP and SUI, and the application of mesh in reconstructive surgery. Results Three hundred and thirty-four IUGA members responded to the survey; most of the responses were from Europe (40 %) and North America (23 %). After the FDA safety communication regarding serious complications of using transvaginal mesh, 45 % of responders reported decreased use of mesh, while 31 % reported that it had no effect or that they did not use mesh for transvaginal prolapse (23.6 %). Regarding the evaluation and treatment of SUI, 51 % of responders would perform urodynamics (UDS) before surgical correction of uncomplicated SUI and 78.5 % of responders would perform UDS if no urine leakage was demonstrated on examination. The preferred method of treatment for SUI is midurethral sling (MUS), regardless of prior treatments (65.1 %), concomitant surgeries (74.5 %), or examination findings (50.8–92.6 %). Regarding POP repair, the preferred approach for apical (61 %) and posterior (99.4 %) prolapse repair is vaginal. Conclusions Most respondents use a vaginal approach for POP surgery. The FDA safety communication regarding serious complications related to the use of transvaginal mesh for prolapse surgery led to a global decrease in the employment of mesh for POP. Synthetic midurethral slings are predominant in the current treatment of SUI. Despite new recommendations, many responders still perform UDS for uncomplicated SUI.